2017
DOI: 10.1186/s12992-017-0241-9
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-border movement of older patients: a descriptive study on health service use of Japanese retirees in Thailand

Abstract: BackgroundThailand’s policy to promote long-stay tourism encourages Japanese retirees to relocate to Thailand. One concern of such an influx is the impact of these elderly foreign residents on the Thai health system. This study aims to reveal the current use of and needs for health services amongst Japanese retirees residing in various locations in Thailand.MethodsIn collaboration with nine Japanese self-help clubs in Bangkok, Chiang Mai, Chiang Rai, and Phuket, questionnaire surveys of Japanese long-stay reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
(24 reference statements)
3
20
0
Order By: Relevance
“…Our previous analysis revealed that Japanese retirees' use of health services in Thailand was infrequent and primarily for nonserious conditions [30]. This study provides additional information as to individual factors of all the categories -predisposing, enabling and need factor -affecting their health seeking behavior.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Our previous analysis revealed that Japanese retirees' use of health services in Thailand was infrequent and primarily for nonserious conditions [30]. This study provides additional information as to individual factors of all the categories -predisposing, enabling and need factor -affecting their health seeking behavior.…”
Section: Discussionmentioning
confidence: 73%
“…because they went to Japan for treatment, they stay Thailand shorter. This was revealed by our previous study [30] as well as a study in Malaysia [26] which indicated that voluntary health repatriation to Japan would reduce medical service use in a retirement place.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nonetheless, there are concerns about the effects of medical tourism on the health system, such as through internal migration of healthcare professionals, burdens created by foreign retirees seeking long-term end-of-life care, and cost inflation for the local population [21,87,[89][90][91]. A range of policy prescriptions have been offeredintegrated human resource planning, increased private sector contribution to human resource development, lifting restrictions on the recruitment of international medical graduates, levying a medical tourist tax to transfer some of the commercial gains from medical tourism to the health system, and reviewing policies for long-stay tourism.…”
Section: Thailandmentioning
confidence: 99%
“…In the original publication of this article [1], published on 8 March 2017, figure 2 and 3 contained a wrong figure caption. The original captions are as followed: The original publication of this article has been corrected.…”
Section: Erratummentioning
confidence: 99%